2019
DOI: 10.1016/j.jaci.2019.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Role of the IgE variable heavy chain in FcεRIα and superantigen binding in allergy and immunotherapy

Abstract: Background: Variable heavy chain (VH) family frameworks (FWRs) have been reported to affect antibody receptor and superantigen binding; however, such effects in IgE remain largely unknown. Given that VH family biases have been previously reported in IgE of certain allergies, there is a need to investigate this phenomenon for biotechnological and therapeutic purposes. Objective: We sought to investigate the effects of VH families on IgE interaction with FcεRIa, anti-IgE omalizumab, antigen, and superantigen pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
74
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 62 publications
10
74
0
Order By: Relevance
“…21,24,34,35 Previous experimental and computational studies of IgG and IgA have suggested that the Fc and Fab regions of an antibody might communicate with one another; 23,25 for example, point mutations in the Fc region may reduce binding affinity, whilst antigen binding to the Fab region changes the conformation of the Fc domain to promote binding to its receptor. 22,24,36,37 Allostery between the different subunits in a multimeric IgM, however, remains elusive. Our multiscale simulation study indicates that the individual Fab domains are free to move independently of one another and do not affect the motion of their neighbors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,24,34,35 Previous experimental and computational studies of IgG and IgA have suggested that the Fc and Fab regions of an antibody might communicate with one another; 23,25 for example, point mutations in the Fc region may reduce binding affinity, whilst antigen binding to the Fab region changes the conformation of the Fc domain to promote binding to its receptor. 22,24,36,37 Allostery between the different subunits in a multimeric IgM, however, remains elusive. Our multiscale simulation study indicates that the individual Fab domains are free to move independently of one another and do not affect the motion of their neighbors.…”
Section: Discussionmentioning
confidence: 99%
“…A molecular-level understanding of how such distinct binding avidities arise for the same antigen is of importance for future design of therapeutic antibodies and epitope selection. Given that we have previously showed that antibody-antigen interactions can be drastically affected by small changes in the antibody light chain, 21 antibody hinge, 22 V-region pairing, 23 and VH families, 24 it may be necessary to study the whole IgM molecule using a holistic approach. 25 Thus, we now report the rst integrative models of fulllength Pertuzumab and Trastuzumab IgM multimers, based initially on available X-ray and NMR structures for each Ig domain.…”
Section: Introductionmentioning
confidence: 99%
“…Since viruses can develop cross-resistance to multiple drugs [21,43], and Y183 has yet to have a reported clinical mutation, compound 2 serves as a potentially important guide for targeting drug-resistant HIV-1 variants, and with the conservation of the site across RTs -a possible broad-spectrum RTI as well. By taking a holistic approach [44] in studying the whole structure of the target proteins and looking for common sites and how resistance develops, as demonstrated for HIV-1 Gag [45], HIV-1 Protease [43], and antibodies [46][47][48][49][50][51], the search for common druggable conserved sites across protein families can add to the success of developing broad-spectrum therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…While less frequent than in type IV, nickel could elicit type I hypersensitivity through "nonantigenic" mechanism via IgE (Malo et al, 1985) and was postulated to act as a mast cell discharger (Walsh et al, 2010). It is possible that Ni 2+ binding may involve mechanisms apart from CDRs alone, requiring a whole antibody holistic investigation (Phua et al, 2019) given that the various regions of the antibody interact together to affect antigen binding (Lua et al, 2018;Su et al, 2018) and even receptor engagement (Ling et al, 2018;Lua et al, 2019), with the possibility of these regions coming synergistically to form histidine rich areas to bind Ni 2+ .…”
Section: Introductionmentioning
confidence: 99%